2018
DOI: 10.1136/bmjgh-2018-000917
|View full text |Cite
|
Sign up to set email alerts
|

Strategic purchasing for universal health coverage: examining the purchaser–provider relationship within a social health insurance scheme in Nigeria

Abstract: BackgroundIn an attempt to achieve universal health coverage, Nigeria introduced a number of health insurance schemes. One of them, the Formal Sector Social Health Insurance Programme (FSSHIP), was launched in 2005 to provide health cover to federal government and formal private sector employees. It operates with two levels of purchasers, the National Health Insurance Scheme (NHIS) and health maintenance organisations (HMOs). This study critically assesses purchasing arrangements between NHIS, HMOs and healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 15 publications
0
56
0
Order By: Relevance
“…The findings of this study identified gaps in health service responsiveness performances, indicating that they failed to meet the expectations of almost half of the clients receiving care within the NHIS regarding how they should be treated and the convenience of the environments in which they were treated. A qualitative study carried out in the study setting suggested that the way the insured users are treated might have affected the perceptions of clients towards responsiveness and their satisfaction with services (Etiaba et al, 2018). In general, this present study suggests the need to improve the responsiveness performances in UNTH which may require targeted interventions like training of healthcare workers, supportive supervision and on-site mentoring and technical assistance.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The findings of this study identified gaps in health service responsiveness performances, indicating that they failed to meet the expectations of almost half of the clients receiving care within the NHIS regarding how they should be treated and the convenience of the environments in which they were treated. A qualitative study carried out in the study setting suggested that the way the insured users are treated might have affected the perceptions of clients towards responsiveness and their satisfaction with services (Etiaba et al, 2018). In general, this present study suggests the need to improve the responsiveness performances in UNTH which may require targeted interventions like training of healthcare workers, supportive supervision and on-site mentoring and technical assistance.…”
Section: Discussionmentioning
confidence: 73%
“…Rao (2008) proposes that there could be perverse interests to provide low quality of care over-diagnose or under-treat for making profits, but if there is a strong monitoring and evaluation it would solve some of these issues that cause dissatisfaction. Some of these concerns has been alluded to by the clients' who participated in a qualitative study in Enugu (Etiaba et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Delayed payments affect health facility operations and may lead to providers either turning away enrolees or charging them informal fees. This has been reported in different settings such as Ghana and Nigeria ( Dalinjong and Laar, 2012 ; Etiaba et al , 2018 ; Suchman, 2018 ).…”
Section: Discussionmentioning
confidence: 54%
“… Sieverding et al (2018) found that Kenyan private providers perceived NHIF capitation rates per enrolee as inadequate. In Nigeria, Etiaba et al (2018) also note that capitation rate from the Formal Sector Social Health Insurance Program of the National Health Insurance Scheme was deemed inadequate by public and private providers. However, it has been reported that the perception by healthcare providers in Kenya that capitation rates are low may be because of their limited understanding of how a capitation payment mechanism works ( Obadha et al , 2019c ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the very purpose of strategic purchasing for health is to give the purchaser (the SHIs) power to elicit quality through payment. In the context of strategic purchasing, the literature suggests this is best done by setting clear guidelines, and putting strong systems in place to monitor provider performance and curb corruption [ 71 , 72 ]. Since providers in both Ghana and Kenya value their accreditation status, our data suggests that providers would be motivated to charge correctly if their relationship with the SHIs was partially dependent on this performance measure.…”
Section: Discussionmentioning
confidence: 99%